2007
DOI: 10.1519/r-18055.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Two Warm-Up Protocols on Some Biomechanical Parameters of the Neuromuscular System of MiddleDistance Runners

Abstract: The objective of this study was to determine the effect of 2 different warm-up protocols on the neuromuscular system of well-trained middle distance runners. Seven runners performed 2 different warm-up protocols, one of which included slow running, stretching, and bounding and sprinting exercises, while the other consisted of slow running and stretching only. Before and after warm-up, contractile properties of the vastus lateralis and quadriceps femoris were monitored with a single twitch test, maximal torque,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 0 publications
2
16
1
Order By: Relevance
“…These findings are in-line with those reported recently by Skof and Strojnik (2007) who found an 16% increase in voluntary torque after the completion of a 25-27 min WU procedure incorporating slow running, stretching, bounding and sprinting exercises, whereas strength gains were rather modest (*5%) after a 15 min routine that involved slow running and stretching exercises only. However, direct comparison of the extent of strength gains observed between the present study and the one by Skof and Strojnik (2007) is only anecdotic since subjects' characteristics and structure of the WU routines (i.e., duration, intensity, nature of exercises) vary considerably.…”
Section: Maximal Voluntary Strength and Activationsupporting
confidence: 92%
See 4 more Smart Citations
“…These findings are in-line with those reported recently by Skof and Strojnik (2007) who found an 16% increase in voluntary torque after the completion of a 25-27 min WU procedure incorporating slow running, stretching, bounding and sprinting exercises, whereas strength gains were rather modest (*5%) after a 15 min routine that involved slow running and stretching exercises only. However, direct comparison of the extent of strength gains observed between the present study and the one by Skof and Strojnik (2007) is only anecdotic since subjects' characteristics and structure of the WU routines (i.e., duration, intensity, nature of exercises) vary considerably.…”
Section: Maximal Voluntary Strength and Activationsupporting
confidence: 92%
“…In our experiment, the twitch interpolation technique was adopted to determine potential change in central drive. Although the maximal voluntary activation values estimated here might appear low (*78 to *85% and *80 to *89% for T and C indicate significant main effects of time and condition There was no significant interaction between time and condition PT peak twitch, TPT time to peak twitch, HRT half-relaxation time, MRFD maximal rate of twitch force development, MRFR maximal rate of twitch force relaxation * P \ 0.05, for statistically significant differences between values recorded before and after the warm-up Eur J Appl Physiol (2009) 106:573-581 577 R WU and S WU , respectively), there are in-line with previous studies where incomplete activation of the KE muscles has also been reported (Girard et al 2008;Skof and Strojnik 2007). An important result was also the strong correlation found between increases in MVC torque and muscle activation after each WU protocol.…”
Section: Maximal Voluntary Strength and Activationsupporting
confidence: 82%
See 3 more Smart Citations